Placental histopathology in late preterm infants: clinical implications - Kristina Ericksen; Joshua Fogel; Rita P. Verma (The Korean Pediatric Society, 2020)
Background The etiopathogenesis of late preterm (LPT) birth is undetermined. Placental histopathology, which reflects an adverse intrauterine environment and is reportedly associated with preterm labor and neonatal morbidities, has not been studied in LPT infants. Purpose We investigated placental pathological lesion as markers of an adverse intrauterine environment during LPT labor. Methods This retrospective case-control study compared placental histopathological and clinical variables between LPT and term neonates. Placental variables included chorioamnionitis, funisitis, hemorrhage, abruption, infarction, calcification, and syncytial knots. Maternal variables included age, substance abuse, pregnancyassociated diabetes mellitus and hypertension, duration of rupture of membrane, antibiotic use, and magnesium sulfate, whereas, those of neonates included gestational age, birth weight, race, sex, and Apgar scores. Standard statistical proedures were applied to analyze the data. Results Chorioamnionitis (50% vs. 17.8%, P<0.001) and funisitis (20% vs. 4.4%, P=0.002) were more common in term infants. Placental infarction rate was insignificantly higher in LPT infants (25.6% vs. 14.3%, P=0.08). The mothers in the LPT group were older (30.4 years vs. 28.1 years, P=0.05; odds ratio [OR], 1.06; 95% confidence interval [CI], 0.998-1.12, P=0.056) and more often suffered from hypertension (28.9 vs. 12.9 %, P=0.02), and received magnesium sulfate (48.9 vs. 20%, P< 0.001; OR, 2.86; 95% CI, 1.12-7.29, P<0.05). Duration of rupture of membrane was higher in term infants (13.6 hours vs. 9.1 hours, P<0.001). Chorioamnionitis (OR, 0.33; 95% CI, 0.13-0.79; P<0.05) was associated with a lower risk of LPT delivery. Conclusion Placental infection is not a risk factor for LPT births. There is a nonsignificant predominance of vascular anomalies in LPT placentas. Higher maternal age, magnesium sulfate therapy, and maternal hypertension are clinical risk factors for LPT labor.